Assessing the Effect of Human Resource Development on Employee Performance in Nigerian Non-Profit Organizations - Omotayo T Osibanjo; David O. Akinbola; Oluwakemi Onayemi; Fisayo J. Aremu (Universitas Medan Area, 2025)
In the face of the ergonomics of the work environment, the state-of-the-art equipment and raw materials available, which make production possible, human resources are considered the most germane factor that enables production to happen. Employees are regarded as the lifeblood of any organization (for-profit and non-profit alike). However, despite its importance, some organizations still face various difficulties, particularly non-profit organizations, in realizing the advantages of managerial abilities, which include employee career development practices that offer both off-site and on-site opportunities for employees. This study, therefore, examined the effect of human resource development on employee performance in non-profit organizations, focusing on the International Secretariat and the Faith Bible Institute Complex of a selected faith-based organization. The purpose was to analyze how career development, on-site, and off-site training influence employee motivation and performance. A descriptive research design was adopted, and data were collected through structured questionnaires administered to 200 clergy members, both ministerial and non-ministerial. Out of 133 retrieved questionnaires, 108 were valid and analyzed using regression analysis with the Statistical Package for Social Sciences (SPSS). The findings revealed that career development (β = 32.2%), on-site training (β = 18.8%), and off-site training (β = 14.9%) significantly influenced employee motivation at a 0.05 significance level, indicating that these human resource development practices were well implemented, though capable of further improvement. The study implies that management should give due attention to employee welfare, opinions, and initiatives—particularly among lower-level staff—as continuous career development and training opportunities enhance emotional commitment, motivation, and performance, thereby strengthening employees’ affective attachment to the organization.